2020
DOI: 10.18231/2395-1451.2018.0038
|View full text |Cite
|
Sign up to set email alerts
|

RNFL variation in gestational diabetes mellitus: An optical coherence tomography based study

Abstract: To study RNFL thickness in gestational diabetes mellitus based on OCT measurements. Methods: Case-control study with Inclusion criteria: 2groups of age 18-40yrs at 32-34weeks gestation Group 1: Healthy pregnant women Group 2: Pregnant women with GDM Exclusion Criteria: Preexisting hypertension/retinal diseases/renal disease/vascular disease/glaucoma/IOP>21mmHg/cataract/ refractive error correction more than or equal to +/-5D (spherical) or +/-3D (cylinder). Grouping-Study Design: more than 2 unrelated group st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…19,20 Both Acmaz et al and Sasikumar et al postulated that the thinning of the RNFL layer in GDM is due to excessive production of endothelin-1 and PEDF. 7,8 Neurodegenerative process began to occur 7.5 months after introduction of diabetes into their animal 21 We postulate that the transient glucose intolerance effect in our subjects was the reason for no significant difference being found in the mean macular and RNFL thickness in the GDM group. In addition, good treatment compliance, a low HbA1c level, and preexisting normal macular/retinal thickness possibly contributed to our study outcome.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…19,20 Both Acmaz et al and Sasikumar et al postulated that the thinning of the RNFL layer in GDM is due to excessive production of endothelin-1 and PEDF. 7,8 Neurodegenerative process began to occur 7.5 months after introduction of diabetes into their animal 21 We postulate that the transient glucose intolerance effect in our subjects was the reason for no significant difference being found in the mean macular and RNFL thickness in the GDM group. In addition, good treatment compliance, a low HbA1c level, and preexisting normal macular/retinal thickness possibly contributed to our study outcome.…”
Section: Discussionmentioning
confidence: 74%
“…They measured mean RNFL thickness in 176 pregnant women with GDM and 188 healthy pregnant women in India during their third trimester of pregnancy using the Cirrus HD OCT, 8 which was similar to the OCT system used in our study. Acmaz et al also reported contrary results to ours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations